Development and evaluation of a new multidimensional oral health indicator - Mendes, José João; Santos, Rui; Lyra, Patrícia; Delgado, Ana Sintra; Machado, Vanessa; Botelho, João; Proença, Luís (Frontiers in Oral Health, 2025)
AimTo develop a new multidimensional oral health indicator (MOHi) to ascertain and characterize overall oral health status.Materials and MethodsMOHi was developed using data from first-time patients (N = 1,034) attending a university dental clinic over an 18-month period. Participants completed the Oral Health Value Scale (OHVS), the Oral Health Impact Profile-14 (OHIP-14) and self-reported periodontal status questionnaires. Caries experience through Decayed, Missing and Filled Teeth (DMFT) index, was combined with radiographs. MOHi was built as a linear combination of the normalized OHVS, OHIP-14 and DMFT scores, in a continuous scale from 0 to 3, with higher scores representing a more degraded oral health condition. MOHi was evaluated according to sociodemographic, behavioral characteristics, and periodontal self-reported status. We compared MOHi mean values with t- Student's test and ANOVA one-way. Stepwise multivariate logistic regression methodologies modelled MOHi and identified significant predictors. Model performance was evaluated by ROC/AUC analysis.ResultsMOHi had a normal distribution adequacy (ranging 0.29–2.47), with an average of 1.22 (±0.41). Significantly higher MOHi scores were found in patients with self-reported periodontitis (p < 0.001), former/active smokers (p < 0.001), elementary/middle education level (p < 0.001), employed/retired (p < 0.001), age >= 45 years (p < 0.001) and married/divorced/widowed (p < 0.001). The final reduced logistic regression model identified age (OR = 1.05), self-reported periodontitis (OR = 1.94), sex—female (OR = 1.80), smoking status active/former (OR = 3.12/OR = 1.62), education level—elementary/middle (OR = 2.94/OR = 2.27) as predictor conditions towards a more degraded oral health condition (AUC = 0.81).ConclusionMOHi has shown to be a promising tool to comprehensively characterize the overall oral health status.